2005
DOI: 10.1136/adc.2005.084285
|View full text |Cite
|
Sign up to set email alerts
|

Protein substitute dosage in PKU: how much do young patients need?

Abstract: Background: The optimal dose of protein substitute has not been determined in children with phenylketonuria (PKU). Aim: To determine if a lower dose of protein substitute could achieve the same or better degree of blood phenylalanine control when compared to the dosage recommended by the UK MRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…Blood Phe concentrations can be misleading unless carried out repeatedly at regular intervals; some patients will deliberately lower their Phe intake just prior to blood sampling; others delay sampling if they know their Phe concentration is likely to be high. Other factors, such as infections, intra-and interday variations in blood Phe concentrations (MacDonald et al 1998;van Spronsen et al 1993;van Spronsen et al 1996), energy intake, and dosage and timing of protein substitute (MacDonald et al 2006c), may affect the interpretation of results (Fig. 1).…”
Section: Compliance Measures In Pkumentioning
confidence: 94%
“…Blood Phe concentrations can be misleading unless carried out repeatedly at regular intervals; some patients will deliberately lower their Phe intake just prior to blood sampling; others delay sampling if they know their Phe concentration is likely to be high. Other factors, such as infections, intra-and interday variations in blood Phe concentrations (MacDonald et al 1998;van Spronsen et al 1993;van Spronsen et al 1996), energy intake, and dosage and timing of protein substitute (MacDonald et al 2006c), may affect the interpretation of results (Fig. 1).…”
Section: Compliance Measures In Pkumentioning
confidence: 94%
“…It is critical for patients with PKU to take the prescribed amount of medical formula each day. The formula is usually consumed approximately three to four times a day, and sometimes up to six times a day, depending on individual requirements [2,3]. As children with PKU derive less protein from foods, it is necessary for them to consume more carbohydrates and fats to supplement their energy.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylalanine-free amino acid modules typically provide 80 to 85 percent of an individual's daily protein requirements in addition to necessary macro-and micronutrients. However, the optimal dosage has yet to be determined (MacDonald et al 2006). It has been hypothesized that a higher amount of protein substitute (2 g/kg/day) may lead to increased protein retention and compensate for the potential for poor utilization of free amino acids.…”
Section: Dietary Therapymentioning
confidence: 99%
“…It has been hypothesized that a higher amount of protein substitute (2 g/kg/day) may lead to increased protein retention and compensate for the potential for poor utilization of free amino acids. Free amino acids are absorbed and oxidized faster than natural protein; therefore medical formula should be divided into three doses per day to enhance utilization of amino acids (MacDonald et al 2006;. MacDonald et al (2006) showed improved Phe control for those taking 2 g/kg/day of protein substitute compared to those taking 1.2 g/kg/day.…”
Section: Dietary Therapymentioning
confidence: 99%
See 1 more Smart Citation